Effects of telmisartan and losartan on left ventricular mass in mild-to-moderate hypertension. A randomized, double-blind trial - Martina, Benedict; Dieterle, Thomas; Sigle, Jörg-Peter; Surber, Christian; Battegay, Edouard (Cardiology, 2003)
Copyright © 2003 S. Karger AG, Basel